2022
DOI: 10.1007/s12311-022-01473-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Recordings of the Cerebellum in Movement Disorders

Abstract: The cerebellum plays an important role in movement disorders, specifically in symptoms of ataxia, tremor, and dystonia. Understanding the physiological signals of the cerebellum contributes to insights into the pathophysiology of these movement disorders and holds promise in advancing therapeutic development. Non-invasive techniques such as electroencephalogram and magnetoencephalogram can record neural signals with high temporal resolution at the millisecond level, which is uniquely suitable to interrogate ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 155 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…Findings were categorized under prevalence statistics (29 studies),[ 15 16 17 18 19 20 21 22 23 ] proposed pathophysiologic mechanisms (15 studies),[ 4 5 6 7 24 25 26 27 28 29 30 ] assessments of psychiatric comorbidities (nine studies),[ 31 32 33 34 35 36 37 38 39 40 ] the stigma associated with tremor disorder (two studies),[ 41 42 ] and evaluations of quality-of-life impact (five studies). [ 36 43 44 45 46 ]…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings were categorized under prevalence statistics (29 studies),[ 15 16 17 18 19 20 21 22 23 ] proposed pathophysiologic mechanisms (15 studies),[ 4 5 6 7 24 25 26 27 28 29 30 ] assessments of psychiatric comorbidities (nine studies),[ 31 32 33 34 35 36 37 38 39 40 ] the stigma associated with tremor disorder (two studies),[ 41 42 ] and evaluations of quality-of-life impact (five studies). [ 36 43 44 45 46 ]…”
Section: R Esultsmentioning
confidence: 99%
“…These implicate aberrant cerebello-thalamo-cortical circuit dysfunction, neurotransmission abnormalities, and genetic variabilities in likely ET pathogenesis. Evidence on rarer disorders was limited, but suggested cerebellar[ 25 26 ] and basal ganglia involvement in dystonic tremor while proposing a central generator for orthostatic tremor. [ 27 ] A summary of other proposed non-parkinsonian tremor disorders is presented in the table.…”
Section: R Esultsmentioning
confidence: 99%
“…From computational neuroanatomy and neuroimaging studies, the premotor, primary motor, parietal regions of the cortex, and cerebellum are believed to be involved in motor control [ 271 ] and tremorous movements [ 101 , 272 ]. Assessing cerebellar activity during motor control and intention tremor tasks could be valuable, especially for patients with cerebellar pathology [ 107 , 273 , 274 ]. For example, recent studies observed heightened cerebellar activity through cerebellar EEG recordings of ET patients [ 105 ] with only one study, to the best of the authors’ knowledge, using an intention tremor task [ 106 ].…”
Section: Conclusion: Future Avenues To Assess Intention Tremormentioning
confidence: 99%
“…Generally speaking, EEG and MEG studies of cerebellar ataxia often utilize the techniques of source localization and functional connectivity analysis ( Kumar et al, 2022 ). Naeije et al used MEG to study intrinsic functional brain network in patients with Friedreich ataxia and found 6 major resting state networks: default mode, sensory motor, language, visual, ventral, and dorsal attention networks, which all connect to the cerebellum.…”
Section: Physiology Measurements In Patients With Cerebellar Ataxia: ...mentioning
confidence: 99%
“…While the above studies often use the techniques of traditional EEG methods, covering mostly cortical area with some cerebellar coverage, recent studies have utilized EEG specifically targeting the cerebellar area ( Kumar et al, 2022 ). For example, a recent study by Govender et al demonstrated cerebellar evoked potential responses in healthy subjects in responses to impulsive accelerations to mastoid and trunks ( Govender et al, 2022 ).…”
Section: Physiology Measurements In Patients With Cerebellar Ataxia: ...mentioning
confidence: 99%